Mismatch prime editing gRNA increased efficiency and reduced indels - Jidong Fei; Dongdong Zhao; Caiyi Pang; Ju Li; Siwei Li; Wentao Qiao; Juan Tan; Changhao Bi; Xueli Zhang (Nature Communications)
Abstract Prime editing enables precise and efficient genome editing, but its efficacy is hindered by pegRNA’s 3’ extension, forming secondary structures due to high complementarity with the protospacer. The continuous presence of the prime editing system also leads to unintended indel formation, raising safety concerns for therapeutic applications. To address these challenges, we develop a mismatched pegRNA (mpegRNA) strategy that introduces mismatched bases into the pegRNA protospacer, reducing complementarity and secondary structure formation, and preventing sustained activity. Our findings show that mpegRNA enhances editing efficiency by up to 2.3 times and reduces indel levels by 76.5% without compromising performance. Combining mpegRNA with epegRNA further increases efficiency up to 14-fold, or 2.4-fold in PE4max/PE5max systems, underscoring its potential in research and therapy. AlphaFold 3 analysis suggests that the optimal mpegRNA structure contributes significantly to improved editing outcomes. Overall, mpegRNA advances prime editing technology, improving efficiency while reducing indels.